2021
DOI: 10.26444/aaem/128017
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia, carbohydrate metabolism disorders and arterial hypertension detected in academic employees during examinations in occupational medicine

Abstract: carbohydrate metabolism disorders and arterial hypertension detected in academic employees during examinations in occupational medicine. Ann Agric Environ Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
1
0
1
Order By: Relevance
“…National recommendations have demanded increased health prevention and promotion efforts in occupational programs (NORA TWU, 2018). Studies conducted in occupational settings have demonstrated the ability for early detection of CVD risk, reduction in CVD RF with behavioral interventions, and overall benefits for the worker, employer, and healthcare system (Andres et al, 2013; Arena et al, 2013; Iakoubova et al, 2019; Marcinkiewicz et al, 2021). Although national and international guidelines remain obscure regarding screening, the need to assess CVD risk for workers in high-risk occupations such as commercial driving remains a current and relevant topic (Apostolopoulos et al, 2013; Parsons et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…National recommendations have demanded increased health prevention and promotion efforts in occupational programs (NORA TWU, 2018). Studies conducted in occupational settings have demonstrated the ability for early detection of CVD risk, reduction in CVD RF with behavioral interventions, and overall benefits for the worker, employer, and healthcare system (Andres et al, 2013; Arena et al, 2013; Iakoubova et al, 2019; Marcinkiewicz et al, 2021). Although national and international guidelines remain obscure regarding screening, the need to assess CVD risk for workers in high-risk occupations such as commercial driving remains a current and relevant topic (Apostolopoulos et al, 2013; Parsons et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Należy też mieć świadomość, że zmniejszenie liczby badań wstępnych i okresowych prowadzi do pogorszenia pierwszo-i drugorzędowej profilaktyki zdrowotnej wśród pracujących, znacznie ograniczając szanse na wykrywanie przy ich okazji nierozpoznanych wcześniej chorób cywilizacyjnych, takich jak nadciśnienie tętnicze, cukrzyca czy dyslipidemie [13,14]. Uwagę zwraca przy tym jeszcze niemal trzykrotny wzrost liczby podejrzeń chorób zawodowych zgłaszanych przez lekarzy medycyny pracy.…”
Section: Wynikiunclassified